Cultural Tourism as a Means of Development of Regional Tourism - Daukaeva Khalida Ibrakhimovna; Mirboboeva Dilfuza Bakhtiyorovna (Indonesian Journal of Cultural and Community Development, 2020)
There is a significant concentration of cultural attractions in a relatively small territory of Uzbekistan, which together with organized cultural events of various kinds are a prerequisite for the development of cultural tourism in the regions of the country. The current study aims to take an in-depth look at cultural tourism, as well as to indicate the prospects and possible aspects of its future development as a means of development of tourism in regions. To achieve the goal, different approaches to the concept of "cultural tourism" were considered, the analysis of the development of this sphere in the world practice, as well as its application in the regions, and the impact of external factors on it was determined. The main problems of development of tourism in the regions can be considered lack of tourist products attracting tourists in the region, poor development of tourist infrastructure. This article investigates types and potential of cultural tourism as an important component of regional tourism, cultural policy and the development of society. The main types of cultural tourism are described, and their potential and importance for the development of regions and for intercultural interaction are outlined. Scientific methods of comparison, generalization and methods of qualitative research were used in the survey. In conclusion of the article the author presents finding of the investigation and describes results.